Gender differences in climate change perceptions and adaptation strategies: An intra-household analysis from rural Kenya - Marther W. Ngigi; Ulrike Mueller; Regina Birner; Alisher Mirzabaev (University of Bonn, Center for Development Research (ZEF), 2016)
It has been widely acknowledged that the effects of climate change are not gender neutral. However, existing studies on adaptation to climate change mainly focus on a comparison of male-headed and female-headed households. Aiming at a more nuanced gender analysis, this study examines how husbands and wives within the same household perceive climate risks and group-based approaches as coping strategies. The data stem from a unique self-collected and intra-household survey involving 156 couples in rural Kenya, where husbands and wives were interviewed separately. Options for adapting to climate change closely interplay with husbands and wives roles and responsibilities, social norms, risk perceptions and access to resources. Consequently, a higher percentage of wives adopt crop-related strategies, whereas husbands employ livestock- and agroforestry-related strategies. Besides, there are gender-specific climate information needs, gendered trust of information and preferred channels of information dissemination. Further, it turned out that group-based approaches benefit husbands and wives differently. Group-based approaches provide avenues for diversifying livelihoods and managing risks for wives, while they are pathways for sharing climate information and adaptation options for husbands. Social groups help husbands and wives to enhance their welfare through accumulating vital types of capital such as livestock, durable assets, human, natural, financial and social capital. The findings suggest that designing gender-sensitive policies and institutionalizing gender in climate change adaptation and mitigation frameworks, are vital. Policy interventions that rely on group-based approaches must reflect gender perspectives on the ground in order to amplify mens and womens specific abilities to manage risks and improve welfare outcomes in the wake of accelerating climate change.
Keywords: D13; J16; Q54; 330; perceptions; adaptation; group-based approaches; gender; intra-household analysis; Kenya